Public policy acceptability: Study on the transfer of management policy for senior high school teachers and teaching personnel in south Sulawesi Province - Zulkhairil, AM; Akib, Haedar; Suradi, Suradi (Linguistics and Culture Review, 2021)
This study aims to analyze the acceptability of the implementation of teacher management transfer policies in South Sulawesi Province. This qualitative descriptive study describes and analyzes the acceptability of teacher management transfer education policies at the Education Office of South Sulawesi Province. The research method with a descriptive approach. Data was collected by interviewing teachers and implementers involved in implementing the transfer of management policy. The data analysis used is descriptive. The results of the study indicate that the acceptability of teachers and managers of SMA/SMK in South Sulawesi Province shows their acceptance of this policy. From the initial reaction, there were good expectations for the implementation of this policy, even though there were still some obstacles at the beginning of the management process, such as late salaries that occurred due to changes in administrative processes and coordination across districts geographically, South Sulawesi Province was quite extensive.